Association of Metabolic Syndrome With Kidney Function and Histology in Living Kidney Donors. Issue 9 (19th July 2013) - Ohashi, Y.; Thomas, G.; Nurko, S.; Stephany, B.; Fatica, R.; Chiesa, A.; Rule, A. D.; Srinivas, T.; Schold, J. D.; Navaneethan, S. D.; Poggio, E. D.
Abstract The selection of living kidney donors is based on a formal evaluation of the state of health. However, this spectrum of health includes subtle metabolic derangements that can cluster as metabolic syndrome. We studied the association of metabolic syndrome with kidney function and histology in 410 donors from 2005 to 2012, of whom 178 donors were systematically followed after donation since 2009. Metabolic syndrome was defined as per the NCEP ATPIII criteria, but using a BMI > 25 kg/m2 instead of waist circumference. Following donation, donors received counseling on lifestyle modification. Metabolic syndrome was present in 50 (12.2%) donors. Donors with metabolic syndrome were more likely to have chronic histological changes on implant biopsies than donors with no metabolic syndrome (29.0% vs. 9.3%, p < 0.001). This finding was associated with impaired kidney function recovery following donation. At last follow‐up, reversal of metabolic syndrome was observed in 57.1% of donors with predonation metabolic syndrome, while only 10.8% of donors developed de novo metabolic syndrome (p < 0.001). In conclusion, metabolic syndrome in donors is associated with chronic histological changes, and nephrectomy in these donors was associated with subsequent protracted recovery of kidney function. Importantly, weight loss led to improvement of most abnormalities that define metabolic syndrome.